Consumer reactions to pay-what-you-want and name-your-own-price mechanisms - Wagner, Rafael Luis (2022)
Wagner, R. L., Pacheco, N. A., Basso, K., Rech, E., & Pinto, D. C. (2022). Consumer reactions to pay-what-you-want and name-your-own-price mechanisms. Journal of Consumer Behaviour, 21(4), 641-652. https://doi.org/10.1002/cb.2019 -----------------------------------Funding information: Fundação para a Ciência e a Tecnologia, Grant/Award Number: DSAIPA/DS/0113/2019